Analyzing Driver Response in Real-World Fatal Crashes Using the Event Data Recorder (EDR) - Y. Ahmad; M. A. Mohamad Radzi; S. Mustaffa; K. A. Abu Kassim; M. S. Ramli (Journal of the Society of Automotive Engineers Malaysia, 2022)
Using the information stored in the Event Data Recorder (EDR), crash researchers have been able to offer objective analyses regarding vehicle performance and driver response in road crash events. Several research on the use of the crash data retrieval system in pedestrian accidents posited that EDRs had become an important source for crash researchers to investigate road crashes involving data recorder-equipped vehicles. In Malaysia, a previous MIROS study was able to determine the probable causes of various crashes involving a certain car brand using both the road crash event data obtained on-site and from in-vehicle EDRs. In this particular study, a total of 16 real-world fatal crash cases from 2019 to 2021 involving EDR-equipped passenger cars were investigated to retrieve the necessary information regarding the driver’s response with regard to braking, accelerating, and steering control in the 5-second period prior to the crashes. The 16 cases represented 16 drivers who had been involved in the fatal crash. The in-vehicle event data was successfully retrieved using Crash Data Retrieval (CDR) tools either from the onboard diagnostics (OBD) system or through the ’direct method’. The study indicated most drivers (36.4%) applied the brake only one second before impact whereas 9.1% of them did not apply the brake. It was also found that 23.1% of the drivers pressed down the accelerator pedal and did not apply the brake upon impact while 15.4% of the drivers did not react before crashing (neither accelerated nor applied the brake). Unfortunately, data for steering control could not be retrieved as it was not stored in the EDR (older models). The findings are expected to help crash researchers to better understand the use of EDRs in determining the various calculations in car crashes.